Ikalan Layanan Masyarakat Tentang Bahaya Penggunaan Telepon Selular saat Berkendara - Efrizal Hardiman; Happy Yugo Prasetya; Meyti Eka Apriyani (JURNAL INTEGRASI, 2014)
The number of Traffic accidents in Indonesia is still in high number, it because the lack of awareness of the people to be careful while driving. The negative effects of traffic accidents are causing national econo mic loss by 2,9% from Gross Domestic Product. One of the traffic accidents factor are loss of concentration while driving. The cause of loss of concentration is there is an attention diversion that using hand phone while driving. Therefore it is necessary to dissemination to the public to be more cautious while driving through advertisements. The selection of public service ad is quite effective because it has the definition of non-commercial ads which the purpose is to influence audiences to behave in accordance with the advertising message. Based on the test results of the 50 respondents,total of 29 respondents had positive response on public service ad that have been made.